Isolated splenic metastasis from primary fallopian tube carcinoma and the application of laparoscopic splenectomy: a case report and literature review - Kang, Dongxue; Zhao, Danyang; Jiang, Xiaodi; Li, Deming (Frontiers in Oncology, 2023)
Metastases to the spleen from various non-hematologic malignancies are generally not a common clinical event and splenic metastases usually mean late dissemination of disease. Solitary splenic metastases from solid neoplasm are extremely uncommon. Furthermore, solitary metastasis to spleen from primary fallopian tube carcinoma (PFTC) is extremely rare and has not been reported in literature. We report a case of isolated splenic metastasis in a 60-year-old woman, occurring 13 months after total hysterectomy, bilateral salpingo-oophorectomy, pelvic lymphadenectomy, paraaortic lymphadenectomy, omentectomy and appendectomy were performed for PFTC, whose serum tumor marker CA125 raised to 49.25U/ml (N < 35.0 U/ml). The abdominal computed tomography (CT) scan revealed a 4.0×3.0 cm low-density lesion in spleen which was suspicious for malignancy and no lymphadenectasis or distant metastasis. The patient underwent a laparoscopic exploration, and one lesion was found in the spleen. And then the laparoscopic splenectomy (LS) underwent. He histopathological diagnosis confirmed the suspect of splenic metastasis from PFTC Histopathological diagnosis showed that the splenic lesion was a high-differentiated serous carcinoma from PFTC metastasis. The patient has recovered for over 1 year, with no tumor recurrence. This is the first reported case of isolated splenic metastasis from PFTC. This case underlines the importance of serum tumor marker assessment, medical imaging examination and history of malignancy during follow-up and laparoscopic splenectomy seems to be the optimal approach for isolated splenic metastasis from PFTC.